The Indonesian Government's Political Control of the Islamic Ideology Movement in a Country with a Majority of Muslims - , Ristapawa Indra; , Martin Kustati; , Fitrah Santosa (Archives of Current Research International, 2021)
Geneological perspective differences on the Jakarta Charter had become the main cause for some Islamic groups to have an endless struggle in embodying Islamism and Islamic ideology formalism as the basis of their philosophy and ideology. Compromise and radicalism are part of the movement of these groups. This study aims to examine the supporters’ movement of the understanding of Islamism and Islamic Idiology formalism in order to get involve in Indonesian political system. The phenomenological constructivism approach is used in understanding the views of New Order Regime and Reforms Regime in dealing with Islamism and Islamic idiology formalism which are taken from interview and document analysis. The results of the study show that the radical issues are far more than the normal level of the Indonesian Islam movement. The concerns of certain groups which are oriented towards the Islamic movement in Indonesia are more co-opted in an anti-Islamic global network sponsored by the United States. The status of the New Order Regime and the Reform Regime do not differ significantly in addressing various state issues related to the issues of the Islamic movement. For these two regimes, Islamism is still seen as a movement that must be tightly controlled, radical issues and terrorism are the most effective political instruments for controlling Islamic nationalism groups whose views differ from secular nationalist groups with regard to national philosophy and identity.